Análisis y diseño de la red para la nueva unidad educativa del milenio Leopoldo Lucero para la empresa Azuldata - Ocampo Lucero, Carlos Fabián (2016)
The Leopoldo Lucero educational unit lacks network's infrastructure, so that it needs one of them to solve its needs, like: Internet access in whole school, at least a data outlet in every classroom, vertical cabling (backbone) that interconnects with all buildings, an equipment room, video conferencing service (Point-to-point or multipoint), IP telephony with interactive voice response (IVR), and transfer file service's. The network was designed under the hierarchical design scheme (core, distribution and access), by applying the top-down methodology, where begin with the user needs, applications, IP addressing, VLAN; and in the physical layer, the ANSI/TIA/EIA cabling standards were applied. E.g.: in the fiber optic backbone, and, in cable F/UTP, category 6A, that was used in the buildings with a low density of data outlets. The link of fiber optic was evaluated for its attenuation and link margin. Also was determined the amount of cabinets throughout the school, the minimum bandwidth required at the peak hour for Internet service. As the cabling keeps the ANSI/EIA/TIA standards supports all network services. Besides, It was determined a minimum bandwidth 10 Mbps toward internet at the peak hour. Finally, the cost analysis showed a required budget of 374 340.63 US dollars to implement the network.